2021
DOI: 10.1177/17411432211034174
|View full text |Cite
|
Sign up to set email alerts
|

Principals’ perceptions of school autonomy and educational leadership

Abstract: This paper examines principals’ perceptions of school autonomy and leadership as part of a 3-year research project looking at the implications of school autonomy on social justice across four states of Australia (Victoria, New South Wales, Western Australia and Queensland). Drawing on interviews with principals and representatives from principal stakeholder organisations in these four state jurisdictions, the paper identifies a number of key issues for school principals and the implications for understandings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Similarly, Prado Tuma and Spillaen (2019) found that principals struggle to make sense of external stakeholders' demands that they perceive to conflict with their own understanding of the goals and values of the school. Furthermore, principals often need to deal with long and time-consuming construction-related issues they do not have training for, without any professional assistance, which takes time away from tasks they consider to be more relevant (Collie et al, 2020;Niesche et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Prado Tuma and Spillaen (2019) found that principals struggle to make sense of external stakeholders' demands that they perceive to conflict with their own understanding of the goals and values of the school. Furthermore, principals often need to deal with long and time-consuming construction-related issues they do not have training for, without any professional assistance, which takes time away from tasks they consider to be more relevant (Collie et al, 2020;Niesche et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the growing awareness of the mounting pressure placed on principals, less is known about how school principals experience their work (cf. see Mahfouz, 2020;Niesche et al, 2021). Therefore, the current study aimed to investigate principals' own perceptions of their experienced job demands and resources.…”
Section: Job Demands and Resources Modelmentioning
confidence: 99%
“…The role of the school principal is developing rapidly, not only in Belgium (Flanders) but also in many other Western countries. For example, there is a development toward greater autonomy in school policy, on the one hand, and a growing emphasis on accountability on the other (Niesche et al, 2021). Contemporary social changes such as globalization, migration and increasing diversity also have an important influence on school principals (Fisher, 2014;Mulford, 2010).…”
Section: Burnout Among School Principalsmentioning
confidence: 99%
“…In recent years, research has indicated that work pressure on school principals has increased significantly (ETUCE, 2012;Heffernan, 2018;Niesche et al, 2021). As a result of this evolution, the well-being of school principals is strongly threatened (AGODI, 2016;Walker, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There are serious inequities in Australia’s public school principals’ experiences of autonomy. Career stage, length of time in a particular school or district, and the level of advantage in a school community all play an important role in principals’ sense of autonomy (Heffernan & Pierpoint, 2020 ; Niesche et al, 2021 ).…”
Section: Placing Trust In Principals’ Expertise At the Centre Of Publ...mentioning
confidence: 99%